Fly versus man: evolutionary impairment of nucleolar targeting affects the degradome of Drosophila's Taspase1. Issue 5 (29th January 2015) - Wünsch, Désirée; Hahlbrock, Angelina; Heiselmayer, Christina; Bäcker, Sandra; Heun, Patrick; Goesswein, Dorothee; Stöcker, Walter; Schirmeister, Tanja; Schneider, Günter; Krämer, Oliver H.; Knauer, Shirley K.; Stauber, Roland H.
ABSTRACT: Human Taspase1 is essential for development and cancer by processing critical regulators, such as the mixed‐lineage leukemia protein. Likewise, its ortholog, trithorax, is cleaved by Drosophila Taspase1 (dTaspase1), implementing a functional coevolution. To uncover novel mechanism regulating protease function, we performed a functional analysis of dTaspase1 and its comparison to the human ortholog. dTaspase1 contains an essential nucleophile threonine 195, catalyzing cis cleavage into its α ‐ and β‐subunits. A cell‐based assay combined with alanine scanning mutagenesis demonstrated that the target cleavage motif for dTaspase1 (Q 3 [F/I/L/M] 2 D 1 ↓ G 1′ X 2′ X 3′ ) differs significantly from the human ortholog (Q 3 [F, I, L, V] 2 D 1 ↓G 1′ X 2′ D 3′ D 4′ ), predicting an enlarged degradome containing 70 substrates for Drosophila. In contrast to human Taspase1, dTaspase1 shows no discrete localization to the nucleus/nucleolus due to the lack of the importin‐α/nucleophosmin1 interaction domain (NoLS) conserved in all vertebrates. Consequently, dTaspase1 interacts with neither the Drosophila nucleoplasmin‐like protein nor human nucleophosmin1. The impact of localization on the protease's degradome was confirmed by demonstrating that dTaspase1 did not efficiently process nuclear substrates, such as upstream stimulatory factor 2. However, genetic introduction of the NoLS into dTaspase1 restored its nucleolar localization, nucleophosmin1 interaction, and efficient cleavage of nuclear substrates. We report that evolutionary functional divergence separating vertebrates from invertebrates can be achieved for proteases by a transport/localization‐regulated mechanism.—Wünsch, D., Hahlbrock, A., Heiselmayer, C., Bäcker, S., Heun, P., Goesswein, D., Stöcker, W., Schirmeister, T., Schneider, G., Krämer, O. H., Knauer, S. K., Stauber, R. H. Fly versus man: evolutionary impairment of nucleolar targeting affects the degradome of Drosophila's Taspase1. FASEB J. 29, 1973‐1985 (2015). www.fasebj.org